The European Union deforestation regulation: the impact on Argentina - De La Vega, Pablo (2024)
We analyze the potential economic impacts in Argentina of the European Union Deforestation Regulation (EUDR), which as of January 2025 will prohibit the export to the European Union of certain raw materials and related products if they involve the use of deforested land. A dynamic computable general equilibrium model is used to simulate the impact of such regulation on the Argentine economy. The results suggest that the potential macroeconomic impacts are limited. As a consequence of the EUDR, between 2025 and 2030, GDP would be reduced by an average of 0.46% with respect to the baseline scenario. However, of greater magnitude is the potential environmental impact. Deforested hectares would be reduced by 6.64% and polluting gas emissions by 0.39%.